Minor Clinical Impact of COVID-19 Pandemic on Patients With Primary Immunodeficiency in Israel - Marcus, Nufar; Frizinsky, Shirly; Hagin, David; Ovadia, Adi; Hanna, Suhair; Farkash, Michael; Maoz-Segal, Ramit; Agmon-Levin, Nancy; Broides, Arnon; Nahum, Amit; Rosenberg, Elli; Kuperman, Amir Asher; et al. (Frontiers in Immunology, 2021)
In the last few months the world has witnessed a global pandemic due to severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection causing coronavirus disease 2019 (COVID-19). Obviously, this pandemic affected individuals differently, with a significant impact on populations considered to be at high-risk. One such population, was assumed to be patients with primary genetic defect involving components or pathways of the immune system. While human immunity against COVID-19 is not fully understood, it is, so far, well documented, that both adaptive and innate cells have a critical role in protection against SARS-CoV-2. Here, we aimed to summarize the clinical and laboratory data on primary immunodeficiency (PID) patients in Israel, who were tested positive for SARS-CoV-2, in order to estimate the impact of COVID-19 on such patients. Data was collected from mid-February to end-September. During this time Israel experienced two “waves” of COVID-19 diseases; the first, from mid-February to mid-May and the second from mid-June and still ongoing at the end of data collection. A total of 20 PID patients, aged 4 months - 60 years, were tested positive for SARS-CoV-2, all but one, were detected during the second wave. 14 of the patients were on routine monthly IVIG replacement therapy at the time of virus detection. None of the patients displayed severe illness and none required hospitalization; moreover, 7/20 patients were completely asymptomatic. Possible explanations for the minimal clinical impact of COVID-19 pandemic observed in our PID patients include high level of awareness, extra-precautions and even self-isolation. It is also possible that only specific immune pathways (e.g. type I interferon signaling), may increase the risk for a more severe course of disease and these are not affected in many of the PID patients. In some cases, lack of an immune response actually may be a protective measure against the development of COVID-19 sequelae.